2002
DOI: 10.1002/mus.10285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of FK506 on myasthenia gravis patients with high interleukin‐2 productivity in peripheral blood mononuclear cells

Abstract: We compared the early effects of FK506 on clinical severity, interleukin-2 (IL-2) production by phytohemagglutinin-stimulated peripheral blood mononuclear cells (PBMs), and serum levels of acetylcholine receptor antibodies between myasthenia gravis (MG) patients with elevated (>1250 pg/ml, n = 9) or normal (<1250 pg/mL, n = 10) levels of PBM IL-2 production. Reduction in clinical severity and PBM IL-2 production were significantly greater in the patients with elevated IL-2 production than those with normal PBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
3
13
2
1
Order By: Relevance
“…None of the patients exhibited significant side effects up to 1 year into the treatment, which is consistent with previous reports [9,10,11], probably because of the low-dose administration (daily dose of 3 mg) of FK506 [8]. Furthermore, among the 18 patients treated with FK506, 4 patients (22%) maintained MM sufficiently with FK506 alone during the follow-up phase (severity score: 6.2 ± 3.3 before treatment; 1.3 ± 1.1 at 1 year).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…None of the patients exhibited significant side effects up to 1 year into the treatment, which is consistent with previous reports [9,10,11], probably because of the low-dose administration (daily dose of 3 mg) of FK506 [8]. Furthermore, among the 18 patients treated with FK506, 4 patients (22%) maintained MM sufficiently with FK506 alone during the follow-up phase (severity score: 6.2 ± 3.3 before treatment; 1.3 ± 1.1 at 1 year).…”
Section: Discussionsupporting
confidence: 81%
“…Among the 4 patients who maintained MM sufficiently with FK506 alone, 3 exhibited elevated PBM IL-2 production (>1,250 pg/ml [15]) before treatment, generalized symptoms of MG and elevated serum AChR Ab titer. This appears consistent with previous reports that MG patients with elevated PBM IL-2 production exhibited immediate effects after FK506, with clinical characteristics including generalized symptoms of MG and serum AChR-Ab positivity [11, 15]. …”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Tacrolimus is known to be 10-100-fold more active than cyclosporin A in all parameters of specific T cell inhibition (6,7). Recently, Utsugisawa et al reported that this treatment was significantly effective in MG patients with high Il-2 productivity in peripheral blood mononuclear cells (PBMC) (8). They reported that clinical improvement with tacrolimus was achieved so rapidly that lower-limb muscle strength improved 2 weeks after the start of administration.…”
Section: Discussionmentioning
confidence: 99%